Kritis, Objektif, dan Emansipasitoris: Relevansi Realisme Kritis Roy Bhaskar bagi Studi Agama - Yohanes Hasiholan Tampubolon; Dody Truna; Rifki Rosyad (Societas Dei: Jurnal Agama dan Masyarakat, 2026)
This article is grounded in the debate over the role of values in the study of religion. Should religious studies be value-free, as argued by McCutcheon, or is value-neutrality impossible, as Goldstein contends? This research departs from that tension and aims to explore how Roy Bhaskar’s critical realism offers a coherent middle path for the discipline. Employing a qualitative literature-based method, the study examines Bhaskar’s works alongside key texts in critical religious studies. The findings show that identifying the colonial, patriarchal, or class-based contexts in which doctrines or rituals emerged is not a moral or political act, but a scientific consequence of causal investigation. Within a Bhaskarian framework, objectivity does not mean value-neutrality; rather, it is an epistemic process aimed at uncovering the mechanisms that shape religious phenomena. Thus, critique of religion is not moralistic but constitutes a component of scientific objectivation. The study finds that the emancipatory dimension of religious studies arises inherently from successful scientific analysis. When mechanisms of oppression, power relations, or ideological structures are revealed, such knowledge becomes emancipatory by virtue of its explanatory power. These insights demonstrate that religious studies can remain critical and objective without slipping into activism or the illusion of pure neutrality.